A=(aij)3×2,ondeaij=(-1)i. (2i-3j)
Soluções para a tarefa
Respondido por
1
Olá,
Lembrando que i= linha e j=coluna
![\left[\begin{array}{ccc}a11&a12\\a21&a22\\a31&a32\end{array}\right] \left[\begin{array}{ccc}a11&a12\\a21&a22\\a31&a32\end{array}\right]](https://tex.z-dn.net/?f=++%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Da11%26amp%3Ba12%5C%5Ca21%26amp%3Ba22%5C%5Ca31%26amp%3Ba32%5Cend%7Barray%7D%5Cright%5D+)
a11= (-1*1)*(2-3) = -1*-1= 1
a12= (-1*1)*(2-6) = -1*-4= 4
a21= (-1*2)*(4-3) = -2*1= -2
a22= (-1*2)*(4-6) = -2*-2= 4
a31 = (-1*3)*(6-3) = -3*3= -9
a32 = (-1*3)*(6-6) = -3*0= 0
Portanto a matriz fica
![A=\left[\begin{array}{ccc}1&4\\-2&4\\-9&0\end{array}\right] A=\left[\begin{array}{ccc}1&4\\-2&4\\-9&0\end{array}\right]](https://tex.z-dn.net/?f=++A%3D%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%26amp%3B4%5C%5C-2%26amp%3B4%5C%5C-9%26amp%3B0%5Cend%7Barray%7D%5Cright%5D+)
Lembrando que i= linha e j=coluna
a11= (-1*1)*(2-3) = -1*-1= 1
a12= (-1*1)*(2-6) = -1*-4= 4
a21= (-1*2)*(4-3) = -2*1= -2
a22= (-1*2)*(4-6) = -2*-2= 4
a31 = (-1*3)*(6-3) = -3*3= -9
a32 = (-1*3)*(6-6) = -3*0= 0
Portanto a matriz fica
Perguntas interessantes
Inglês,
11 meses atrás
Matemática,
11 meses atrás
Biologia,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás